Pengaruh Produk Domestik Bruto (PDB) Sektoral, Suku Bunga Bank Indonesia, dan Suku Bunga Internasional (LIBOR) Terhadap Indeks Harga Saham Sektoral - Fahrul Riza (Journal of Business & Applied Management, 2016)
The influence between the GDP growth number and stock price moves is tenuous. But drilling down to the growth rate in various sectors of GDP can provide some useful insights to investors. This study analyzes the relationship between Gross Domestic Product (GDP), domestic and foreign interest rate and stock prices in Indonesia in the context of Pooled Least Square model. Data were collected quarterly from I/2013 to II/2015 from agricultural, mining, manufacturing, financial-insurance and property-construction sector. The study finds that all variables have negative impact on stock price index. The limitation of this study are lack of other variables such as macro economic indicators which influence the fluctuation of stock price index due to the period of observation was too short.Keywords: GDP, stock price index, interest rate, pooled least square